ACTION EXTRAGONADAL ESTROGEN - Guitelman, Abraham (2015)
This publication will discuss a review of the research and the opinions of scientific groups that have been most devoted to the study of the actions of estrogen on non-sexual organs. This study is necessary because, with the increasing use of these hormones as contraceptives and replacement therapies, it is essential to know the best possible advantages and disadvantages of such treatment can lead to systems which are not directed.